Pengaruh Kompetensi, Kepemimpinan Diri, Sistem Penghargaan, Lingkungan Kerja, Terhadap Komitmen Pada Profesi Dan Profesionalisme Guru SMA Negeri Di Bali - Nengah Sudja, I (Program Doktor Ilmu Ekonomi, 2013)
This research aims to explain the relationships among variables : competence, self leadership, reward systems, work environment; commitment to profession, and professionalizm of teachers of SMAN at Bali. The sample size are 243 teachers who selected by proportional random technique from 12 units of Senior High School Satate at Bali. The tool of analyisis which is used is structural equation model analysis, with supported by AMOS version 19.00 application. The results shows those : (1) the effect of competence to the commitment to profession, is not significant; (2) the self leadership’s effect to the commitment to profession; is not significant also; (3) the effect of reward systems to the commitment to profession is positively significant; (4) the work environment’s effect to the commitment to profession is positively significant; (5) the self leadership’s effect to the professionalizm is not significant; (6) the rewad systems’ effect to professionalizm is positively significant; (7) the effect of work environment to professionalizm is positively significant; (8) the effect of commitment to profession to professionalizm is positively significant. In general, the structural equation model which is accomplished, has passed the criterions of goodness of fit, i.e :: c2 = 276.359; probability of c2 = 0.012; Cmin/DF = 1.749; GFI = 0.923; AGFI = 0.902; RMSEA = 0.056; and TLI = 0.921. Keywords : competence, self leadership, reward systems, work environment; commit-ment to profession, and professionalizm